Pengaruh Penanganan Sweeping Bagasi Terhadap Kepuasan Penumpang Maskapai Citilink Indonesia Di Yogyakarta International Airport - Rara Dianda Saputri (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Baggage sweeping is carried out at the boarding gate unit with the aim of security, convenience and flight safety. And passengers must comply with these regulations so that passengers feel comfortable when in the cabin. Where passengers only carry one luggage weighing 7kg. This research was conducted at Citilink Indonesia at Yogyakarta International Airport. This research is a quantitative study where the data obtained using the questionnaire survey method as wellCostumer Satisfaction Index(CSI) to measure the level of passenger satisfaction with handlingsweeping baggage received. The results of this study can be concluded that the main factors that cause sweeping baggage are passengers who do not want their luggage to be carried or do not want to pay for excess baggage, and the obstacle during sweeping is the lack of understanding of passengers with cabin baggage regulations. The method used by boarding gate officers in dealing with the obstacles that occur is to explain clearly and politely to the passengers concerned regarding the baggage sweeping procedure. The magnitude of the effect of sweeping baggage handling on passenger satisfaction is 56.1% and the remaining 44.9% is influenced by other factors outside of this study. While the level of passenger satisfaction is equal to 46.7% where this figure is in the 3rd criterion, namely quite satisfied.